2015
DOI: 10.1080/14786419.2014.1002405
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and antimicrobial activities of three monocylic sesquiterpenes fromSyringa pinnatifolia

Abstract: We report the isolation of a new sesquiterpene, named as syripinol (1), and two known compounds from the volatile oil of the stems of Syringa pinnatifolia, for the first time. The structures of the isolated compounds were elucidated on the basis of spectroscopic methods including UV, IR, ESI-MS, 1D and 2D NMR techniques. The antibacterial activities of the compounds were also evaluated against various bacteria which showed good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…6A–C). Previous studies found terpenes to be the major pharmacologically active substances in shanchenxiang [7,8,16], and our study found that the key enzyme of terpene biosynthesis was significantly upregulated in wild woody stems compared with cultivated woody stems; these results agree with the observation that the best shanchenxiang for medicinal use is collected from mature wild S. pinnatifolia plants, while the cultivated plants are less medicinally useful. Furthermore, HMGR was highly expressed in fibrous root tissue, which might be related to the environment in which such tissue develops; the fibrous roots are buried in soil, exposing them to a greater range of microorganisms and external stresses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6A–C). Previous studies found terpenes to be the major pharmacologically active substances in shanchenxiang [7,8,16], and our study found that the key enzyme of terpene biosynthesis was significantly upregulated in wild woody stems compared with cultivated woody stems; these results agree with the observation that the best shanchenxiang for medicinal use is collected from mature wild S. pinnatifolia plants, while the cultivated plants are less medicinally useful. Furthermore, HMGR was highly expressed in fibrous root tissue, which might be related to the environment in which such tissue develops; the fibrous roots are buried in soil, exposing them to a greater range of microorganisms and external stresses.…”
Section: Discussionsupporting
confidence: 92%
“…The highest-quality shanchenxiang is derived from mature wild S. pinnatifolia, whose stems are full of purple tyloses accumulated over years [3]. To our knowledge, the wild plants of S. pinnatifolia have a higher concentration of secondary metabolites, especially lignans and sesquiterpenes, than cultivated or young ones [7,[13][14][15][16]. It is known that the anatomical, physiological, and biochemical characteristics of a plant may change with age [17].…”
mentioning
confidence: 99%
“…Zerumbone ( 11 ), syripinol ( 12 ), zerumbone epoxide ( 13 ), mitissimol B ( 14 ), suberosol A ( 15 ), and (4 E ,8 E )-4,7,7-trimethyl-10-oxododeca-4,8-dienal ( 16 ) were also isolated, and these compounds were identified by comparison of their physiochemical data with those previously reported.…”
Section: Resultsmentioning
confidence: 75%
“…The IR absorption bands at 3441, 1635, and 1034 cm –1 indicated the presence of a hydroxy group and a conjugated carbonyl. Analysis of the 13 C NMR spectroscopic data (Table ) showed a close resemblance to those of syripinol ( 12 ) . The major difference was that the two carbons of the Δ 6(7) double bond in 12 were replaced by two sp 3 carbons in 5 .…”
Section: Resultsmentioning
confidence: 82%